Identification of cardiovascular risk factors by infectologists in HIV patients from hospitals of Lima - Valenzuela-Rodríguez, Germán (2019)
Cardiovascular risk factors among patients infected by human immunodeficiency virus (HIV) are important during the follow-up of the disease and must be periodically evaluated. OBJECTIVE. To describe the recognition of cardiovascular risk factors in pa-tients with HIV-infection from infectious disease specialist. MA-TERIALS AND METHODS. A survey was sent to 28 infectologists of five hospitals in Lima. Data on identification of cardiovascular risk factors, families of antiretroviral therapies, frequency of lipid measurement, lipid treatment and cardiovascular risk calculation were obtained. RESULTS. All of the physicians surveyed identified smoking, antiretroviral therapy, arterial hypertension and dyslip-idemia as cardiovascular risk factors. Almost all of the physicians (96%) considered that protease inhibitors were associated with higher cardiovascular risk. But, only 28 % measured the risk. CONCLUSIONS. Infectologists recognized all of the cardiovascular risk factors but these were measured in a small proportion.